THE POLICY OF OVERCROWDING MANAGEMENT OF JAIL IN INDONESIA DURING COVID-19 PANDEMIC - Rudini Hasyim Rado; Nurul Widhanita Yuniar Badilla (STIH Putri Maharaja, 2021)
This research is focused on the overcrowding management policy of jail capacity in Indonesia by utilizing coronavirus disease (covid-19) pandemic momentum. The method of the research is an empiric juridical law method and other related laws and regulations as the primer data confirmed with the observation. Data analysis of the research is based on descriptive analysis. Based on the research data, it might be concluded that the situation in the prisons before the covid-19 pandemic was nationally overcrowding in 102% and it occurred almost all over Indonesia. This overcrowding condition was overloaded and inhuman, moreover in the covid-19 pandemic period. It potentially transmits the disease to the prisoners and officers, thus assimilation policy had been applied by intention to release 40.026 prisoners. It decreases the overcrowding percentage to be 74%. On the other side policy restriction for particular crimes might provide more spaces in the prisons, even though it is hard to be considered effective because overcrowding is still existed.